PENGEMBANGAN APLIKASI KOMPUTER SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN METODE PENEMUAN TERBIMBING PADA MATERI LINGKARAN KELAS VIII - vatricia, susan; maizora, syafdi; syukur, muhammad fachruddin (JP2MS, 2017)
The purpose of this research is to produce Computer Aplication as Media use guided discovery at circle lesson in Class VIII with criteria effectiveness. The type of this research is a research and development by adopting procedure of 4-D. This research done by three stage that is define, design, and develop that consists of validity , practicality, and effectiveness. The instruments of this study were validation sheets, media practicality sheets, and effectiveness sheets. Aplication has with criteria very effectively by the way the students active in the learning process, the good management in the class, can be positive respons, and can be produce the good test.